2020
DOI: 10.2147/ceor.s240183
|View full text |Cite
|
Sign up to set email alerts
|

<p>Economic Evaluation of Dulaglutide vs Traditional Therapies: Implications of the Outcomes of the Rewind Study</p>

Abstract: Background: Diabetes represents a relevant public health problem worldwide due to its growing prevalence and socioeconomic burden, principally due to the development of macrovascular and microvascular complications as well as to the continuous launch of new and even more expensive drugs. The aim of our study is to evaluate the economic impact of dulaglutide, a weekly GLP-1 receptor agonist, on the treatment of diabetic patients as an alternative to both high dose sulphonylureas and insulin basalization at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 39 publications
1
3
0
Order By: Relevance
“…This was attributed to the reduced risks of all-cause mortality and hypoglycemia associated with GLP-1 RA use [ 31 ]. Similar findings were observed in two cost-utility analyses of dulaglutide versus insulin glargine [ 32 , 33 ]. In both studies, dulaglutide was shown to be a cost-effective treatment option for T2D, despite higher annual costs, mainly attributable to pharmacy costs.…”
Section: Discussionsupporting
confidence: 86%
“…This was attributed to the reduced risks of all-cause mortality and hypoglycemia associated with GLP-1 RA use [ 31 ]. Similar findings were observed in two cost-utility analyses of dulaglutide versus insulin glargine [ 32 , 33 ]. In both studies, dulaglutide was shown to be a cost-effective treatment option for T2D, despite higher annual costs, mainly attributable to pharmacy costs.…”
Section: Discussionsupporting
confidence: 86%
“…However, the groups of patients who stopped working and those who continued their usual working activities were not comparable because the latter had a better baseline glucose control than those who stayed at home, and [ 60% were on insulin pump therapy. Users of pump therapy represent approximately 30% of patients with T1D at our clinic, and 13% of T1D patients nationwide [29]. The frequent use of insulin pump therapy among this group of patients is probably related to the fact that most were healthcare workers and/or shift workers who often need pump therapy to cope with their lifestyle and working schedules.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported the cost-effectiveness of dulaglutide as a medication for diabetes [4,18,[20][21][22]. The DISPEL study reported lower medical costs and higher pharmacy costs for patients initiating dulaglutide compared with those initiating basal insulin [4].…”
Section: Discussionmentioning
confidence: 99%